Kuasa Kolase dalam Ekologi Estetika Postmodern - Wahyudi, Nandang Gumelar (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2016)
Nowadays, in the field of art, talking about (art) collage is more than just a technical ma